Stres Kerja Karyawan - Saragih, Yosua Parlindungan; Yunita, Yunita (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2025)
This research aims to present a literature review regarding factors that influence employee work stress. Work stress is the condition of an employee who begins to feel pressure, compulsion, and unease in carrying out his work or in the environment where he works. Cases of work stress have several psychological symptoms that are often found in previous research results, namely intrinsic factors in work, the individual's role in the organization, work relationships, demands from outside work, and personality. The research method uses a systematic literature review. Research data was obtained through internet searches regarding work stress journals with the criteria for articles used, namely those published in the last 5 years, namely from 2019 to 2024. Search for articles via the Researchgate database, Google Scholar, and Google Search with the keywords used: stress, work, and employees. The number of journals analyzed was 13 journals. Data is used to identify and analyze factors that influence employee work stress.  The results of this study conclude that several factors influence work stress, including intrinsic factors in work, the individual's role in the organization, abilities that cannot be used, work relationships, demands from outside work, and personality.